2000
DOI: 10.1212/wnl.55.2.185
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of T1 hypointense lesions in relapsing MS

Abstract: The development of T1 hypointense lesions is strongly influenced by prior inflammatory disease activity, as indicated by enhancing lesions. These results suggest that treatment with once weekly IM IFNbeta-1a (30 mcg) slows the 2-year accumulation of these lesions in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 27 publications
1
75
3
Order By: Relevance
“…Over the last decade, a number of immunomodulatory and immunosuppressive therapies have been approved for clinical use based primarily on demonstration of their ability to suppress focal inflammatory activity, i.e., lesion formation, and clinical relapses (Comi et al, 2001;Leary et al, 2003;Li and Paty, 1999;Li et al, 2001;Miller et al, 1999;Paty and Li, 1993;Simon et al, 1998;Simon et al, 2000;Zhao et al, 2000). Development of these therapies has been critically dependent on MRI because of the ability of MRI to visualize lesion formation with an order of magnitude greater sensitivity than clinical observation is able to detect relapses The number and volume of MS lesions represent the "burden of disease" and are predictive of patients' clinical course over the long term (O'Riordan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, a number of immunomodulatory and immunosuppressive therapies have been approved for clinical use based primarily on demonstration of their ability to suppress focal inflammatory activity, i.e., lesion formation, and clinical relapses (Comi et al, 2001;Leary et al, 2003;Li and Paty, 1999;Li et al, 2001;Miller et al, 1999;Paty and Li, 1993;Simon et al, 1998;Simon et al, 2000;Zhao et al, 2000). Development of these therapies has been critically dependent on MRI because of the ability of MRI to visualize lesion formation with an order of magnitude greater sensitivity than clinical observation is able to detect relapses The number and volume of MS lesions represent the "burden of disease" and are predictive of patients' clinical course over the long term (O'Riordan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, post hoc analysis of MRI data from the MSCRG study of IM IFNβ-1a for MS revealed that treatment with the DMT IM IFNβ-1a reduced T 1 hypointensity formation by 68% versus placebo. 64 In this analysis, the median change from baseline over a 2-year interval in brain MRI T 1 lesion load was 40.0 cubic millimeters ([mm 3 ]; range, -2,424 to 4,042) for patients treated with IFNβ-1a (P = 0.164) and 124.5 mm 3 for placebo (P < 0.001). Although the cohort treated with IM IFNβ-1a showed reduced accumulation of T 1 hypointense lesions over 2 years, this difference was not statistically significant (P = 0.065).…”
Section: ■■ Conclusionmentioning
confidence: 87%
“…Atrophy and neurodegeneration are conditions that are encountered in advanced stages of MS, and they are related to progression of the disease. It has been shown radiologically that long-term use of IMTs might decrease atrophy (32,33,34). Only early-period data (the first 2 years) were included in our study, so atrophy was not evaluated.…”
Section: Discussionmentioning
confidence: 99%